Patterning Biomaterials for the Spatiotemporal Delivery of Bioactive Molecules - Minardi, Silvia; Taraballi, Francesca; Pandolfi, Laura; Tasciotti, Ennio (Frontiers in Bioengineering and Biotechnology, 2016)
The aim of tissue engineering is to promote the repair of functional tissues. For decades, the combined use of biomaterials, growth factors, and stem cells has been at the base of several regeneration strategies. Among these, biomimicry emerged as a robust strategy to efficiently address this clinical challenge. Biomimetic materials, able to recapitulate the composition and architecture of the extracellular matrix, are the materials of choice, for their biocompatibility and higher rate of efficacy. In addition, it has become increasingly clear that restoring the complex biochemical environment of the target tissue is crucial for its regeneration. Towards this aim, the combination of scaffolds and growth factors is required. The advent of nanotechnology significantly impacted the field of tissue engineering by providing new ways to reproduce the complex spatial and temporal biochemical patterns of tissues. This review will present the most recent approaches to finely control the spatiotemporal release of bioactive molecules for various tissue engineering applications.